(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
The university methodological praxis in Latin America shows a tendency towards collaborative and networked work. At the same time, there is also a research culture of urgency, of immediacy in the answers, so it is important that the Latin American University assumes as a challenge the recreation of its capacity to adapt to the contextual needs. This challenge entails a transformation in the missionary functions, including its research work; more specifically, in the application of research methods that in an integrated and convergent way contribute to the understanding of reality. From this referent, the article is oriented to the conception of a proposal for the triangulation of research methods, as a way for the production and validation of knowledge in social sciences. The methodological approach is based on reflexive hermeneutics, by means of focus groups and in- depth interviews, which allow the conferring of meanings to the voices of the actors (experts). The results allow to approach the understanding of triangulation as a theoretical construct, based on the contributions of different disciplines (interdisciplinary perspective). It is concluded that there is a need to resize university research praxis in the field of social sciences, based on the relevance of methodological triangulation as a process associated with knowledge.